Formation period deposits and structures in the Wari complex and surroundings, Huamanga-Ayacucho - Pérez Calderón, Ismael (2021)
Information is presented on a variety of ceramics attributed to early accupations or the Formative period, in variosus deposits, most of which reoccupied in the later periods of the Regional Developments and the Wari Empire, scattered in the área of the cuclear sapace where the city emerged fron Wari. It is therefore a contribution to expand hnowledge an deepen the stady on the origin, development, sapatial distribution and operation of the imperial metropolis